2017
DOI: 10.1007/978-1-4939-7000-1_24
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry and Validation of Macromolecular Structures

Abstract: Macromolecular structure is governed by the strict rules of stereochemistry. Several approaches to the validation of the correctness of the interpretation of crystallographic and NMR data that underlie the models deposited in the PDB are utilized in practice. The stereochemical rules applicable to macromolecular structures are discussed in this chapter. Practical, computer-based methods and tools of verification of how well the models adhere to those established structural principles to assure their quality ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 54 publications
5
38
0
Order By: Relevance
“…The instability index and theoretical PI also suggested that the vaccine is stable and basic in nature and the estimated half-life suggested that the recognized peptide does not possess a short half-life and would remain viable for a span adequate to generate a potential immune response. Vaccine model refinement and validation indicated that quality of the predicted model was good as more than 90% residues were in the favored region [55]. The B-cell continuous epitopes predicted over the surface of the vaccine suggested that the vaccine is capable to get recognized by B-cells indicating its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The instability index and theoretical PI also suggested that the vaccine is stable and basic in nature and the estimated half-life suggested that the recognized peptide does not possess a short half-life and would remain viable for a span adequate to generate a potential immune response. Vaccine model refinement and validation indicated that quality of the predicted model was good as more than 90% residues were in the favored region [55]. The B-cell continuous epitopes predicted over the surface of the vaccine suggested that the vaccine is capable to get recognized by B-cells indicating its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Fitting atoms in an electron density map and building an accurate and reliable model of the investigated molecule is a complex and multi-parameter task. Although many tools are available for evaluating the reliability of a protein structure, based on the analysis of quality of the stereochemistry of the model as well as on the agreement with experimental data [19], quality of the refinement is often summarized with two numbers, the so-called R and R free factors. These values correspond to the ability of the model to explain experimental data, for data that were used for building and refining the model, in the case of the R-factor, or for a subset of the data that was not used to derive the model, in the case of the R free [20].…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“… e R free is typically ∼4–7% higher than R work . The extremely small R free − R wor k difference might indicate a compromised test data set ( Wlodawer et al, 2008 ; Wlodawer, 2017 ). …”
Section: Glutamate Transportersmentioning
confidence: 99%
“…The quality of crystal structures directly depends on the quality of the x-ray diffraction data that were used for their determination. Several articles and reviews describe valuable tools for evaluation of raw experimental data and solved macromolecular structures ( Kleywegt, 2000 ; Wlodawer et al, 2008 ; Chen et al, 2010 ; Gore et al, 2012 ; Adams et al, 2016 ; Wlodawer, 2017 ).…”
Section: Structural Data Quality Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation